HUBUNGAN EFIKASI DIRI DENGAN MOTIVASI BELAJAR SISWA DI SMA PERSATUAN PEDAMARAN - Mardiana Mardiana; Fitri Oviyanti; Baldi Anggara (PAI RAFAH, 2021)
Self-efficacy is the confidance which is in a persom toward his ability to achieve the certain goals successfully and makescontol of the surrounding circumstances to achieve the certain goal successfully. Learning motivation of studens the psychological factor which becomes driving or stimulus to conduct the learning activities acquired throught the common experiences that can change behavior. The population in this study is studens of Persatuan Pedamaran Senior high scool with the all of 102 studens and the sample in this study is 35 of students. Data collection methods used in research using analysis product moment. The result of this indicate that there is a significant relationship between variables self-efficacy with learnig motivation. The result of data analysis are obtained based on calculation and provision a = 0,05 db= n-2 = 33 so it is obtained ttabel 0.447077858 dan thitung 2,852206 atau thitung ≥ ttabel. So the correlation variabel are x and y or relationship self-efficacy and learnig motivation of student in senior high school persatuan significant or Ha received and Ho rejected. Mean the is a significant relationship between self-efficacy with learning motivation of student ini senior high school persatuan.